The teen's musical theatre collection (Young women's ed., 1997)
Beauty and the beast. Beauty and the beast -- Beauty and the beast. Belle (reprise) -- Gentlemen prefer blondes. Diamonds are a girl's best friend -- Mary Poppins. Feed the birds -- The hunchback of Notre Dame. God help the outcasts -- South Pacific. Honey bun -- My fair lady. I could have danced all night -- Flower drum song. I enjoy being a girl -- Annie get your gun. I got the sun in the morning -- The sound of music. I have confidence -- Guys and dolls. I'll know -- Gypsy. If Momma was married (duet) -- Cinderella. In my own little corner -- A date with Judy. It's a most unusual day -- My fair lady. Just you wait -- Oklahoma! Many a new day -- Cats. Memory -- The fantasticks. Much more -- The sound of music. My favorite things -- Les misérables. On my own -- Sleeping beauty. Once upon a dream -- Oklahoma! Out of my dreams -- The little mermaid. Part of your world -- Oklahoma! People will say we're in love -- Camelot. The simple joys of maidenhood -- White Christmas. Sisters (duet) -- The sound of music. Sixteen going on seventeen -- Cinderella. Stepsisters' lament -- Grease. There are worse things I could do -- The phantom of the Opera. Think of me -- The music man. Till there was you -- Song & dance. Unexpected song -- My fair lady. Wouldn't it be loverly.